Estudo do poder antioxidante em infusões de ervas utilizadas como chás - Abreu, Luciana de (2013)
Tea is one of the oldest and most consumed beverages in the world, being mentioned as one of the best sources of phenolic compounds. These substances have been studied especially because they have antioxidant activity. The term refers to tea product herbal infusions the genus Camellia sp. Being that variations in their designations are relative to the type of process that these plants suffer. Antioxidants are substances used to preserve food through the retardation of deterioration, rancidity and discoloration resulting from autoxidation, while biological systems that protect against the damaging effects of reactions of reactive oxygen species. Various methods are used to determine the antioxidant activity of extracts and compounds isolated. One of the most widely used is to evaluate the scavenging activity of the stable free radical DPPH (1,1-diphenyl-2-picryl-hydrazyl). Other methodologies used to evaluate the antioxidant capacity of an extract are the determination of total phenolic compounds, total polyphenol content, and iron reduction technique. In this context, the objective of this study was to determine the content of bioactive compounds, characterized by its value of antioxidant activity, flavonoids and phenolic compounds in different types of tea come from the Camellia sinensis plant, namely: green tea, black tea, white tea, yellow tea and red tea. The experiment was conducted in the post harvest fruit core research, located in the Department of Plant Science, Federal University of Santa Maria, RS. The samples were extracted by infusion sachets of filter paper containing 3 g of the plant in 200 ml of distilled and deionized water by 10 minutes of infusion, at 85 °C. After extraction the samples were placed in glass containers protected from light and stored at a temperature of 0.5 °C. Determination of antioxidant activity by DPPH method was performed by evaluation of polyphenols and flavonoids (colorimetric method), and the chelating activity of Fe+2. As a result, white tea showed the highest antioxidant activity among teas evaluated considering the kidnapping of DPPH. This tea also showed the highest levels of flavonoids and phenolic compounds. Green tea showed higher antioxidant activity as measured by the percentage of ferrous ion chelating activity. Among the 20 types of teas evaluated, hibiscus tea has lowest antioxidant properties. Among the teas originating from Camellia sinensis, the red tea showed the lowest values of antioxidant activity, regardless of the method or evaluation performed, but did not differ from black tea, white and yellow in the percentage of ferrous ion chelating activity. Considering the results of EC50, ilex tea, bilberry and gorse showed intermediate antioxidant power in relation to the Camellia sinensis teas and other teas evaluated in this work.